PERANCANGAN APLIKASI E-LEARNING BERBASIS WEB DENGAN METODE RAPID APPLICATION DEVELOVMENT STUDI KASUS (SMP PLUS BINA TRAMPIL RUMPIN) - Indra Kurniawan; Ferry Agus Sianipar (CV. Multi Kreasi Media, 2022)
The world of education in Indonesia is experiencing difficulties caused by the pandemic, the impact is that the learning mechanism of students is not going well enough. One of the conveniences offered by technology is to present an e-learning system that really helps the learning mechanism in schools throughout Indonesia. SMP Plus Bina Trampil Rumpin is a school that still uses the conventional learning system, namely by meeting face to face. However, since the pandemic, the learning mechanism is no longer carried out face-to-face, instead of using mobile phones, especially in providing material and sending assignments given by the teacher. Making whatsApp groups per class, it is actually not enough to help students overcome their difficulties, because not all students have cellphones as a result, some students cannot follow the online learning mechanism properly. The methods used in data collection are observation, interviews, and literature studies, while the system development uses the rapid application development method. The results that can overcome the existing problems are being able to assist the process of delivering lessons and assisting students in obtaining subject matter via online